2023
DOI: 10.1037/xlm0001215
|View full text |Cite
|
Sign up to set email alerts
|

Age-of-acquisition effects: A literature review.

Abstract: and the current review conclude that AoA effects are likely to have three potential sources: first, due to plasticity mechanisms within the connections between levels of representations (between perceptual/orthography, semantic and/or phonology), second, through the levels of connectivity within the semantic system, and third, competition between concepts within the semantic system, such that a unique concept must be chosen from its competitors or several word candidates). However, within this review we have t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
17
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 263 publications
5
17
0
1
Order By: Relevance
“…Consistent with hypothesis 3, lexicosemantic abilities were the second-best predictor of irregular word reading performances, just after education but largely above dementia severity and other cognitive functions (executive functions and episodic memory). The importance of lexicosemantic abilities in irregular-word reading was further in line with hypothesis 4, as AmNART item success rate was signi cantly predicted by the age of acquisition of irregular words, which has been associated with semantic representations (Juhasz 2005;Elsherif et al, 2023). This is consistent with the fact that NARTlike tests are intended to bypass phonemic decoding by relying more heavily on a person's knowledge of exceptional spelling associated with irregular words.…”
Section: Discussionsupporting
confidence: 73%
“…Consistent with hypothesis 3, lexicosemantic abilities were the second-best predictor of irregular word reading performances, just after education but largely above dementia severity and other cognitive functions (executive functions and episodic memory). The importance of lexicosemantic abilities in irregular-word reading was further in line with hypothesis 4, as AmNART item success rate was signi cantly predicted by the age of acquisition of irregular words, which has been associated with semantic representations (Juhasz 2005;Elsherif et al, 2023). This is consistent with the fact that NARTlike tests are intended to bypass phonemic decoding by relying more heavily on a person's knowledge of exceptional spelling associated with irregular words.…”
Section: Discussionsupporting
confidence: 73%
“…(2003), Bonin, Boyer, Méot, Fayol, and Droit (2004), and Boulenger, Décoppet, Roy, Paulignan, and Nazir (2007). The first four mentioned studies found an AoA effect for both nouns and verbs, all however used an image naming task, and AoA effects are known to be strongly modulated by the imageability of words (Elsherif et al., 2023). The most recent study, Boulenger et al.…”
Section: Discussionmentioning
confidence: 99%
“…First, a broad literature has explored the so-called "AoA effect" which refers to the finding that earlier learnt words are both easier to process for adults (Elsherif, Preece, & Catling, 2023) and more robustly accessible in aphasia patients (Brysbaert & Ellis, 2016). Most studies have looked at the effect specifically with referential nouns; a few exceptions have also considered it with predicates and none have looked at function words, that is, Colombo and Burani (2002), Morrison, Hirsh, and Duggan (2003), Bogka et al (2003), Bonin, Boyer, Méot, Fayol, andDroit (2004), andBoulenger, Décoppet, Roy, Paulignan, andNazir (2007).…”
Section: Broader Theoretical Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, we predict a strong effect of AoA on accuracy and on the RT measures. AoA is related to the performance on practically every word-processing task one can think of (for a recent review, see Elsherif et al, 2022), and there is no reason to think that this will not be the case for spelling. In the PDP model, AoA has the strongest effect when the association between input and output is arbitrary (Lambon Ralph & Ehsan, 2006) but also can have a small and significant effect when the input-output association is quasiregular due to reduced plasticity that occurs as the model develops over time (Monaghan & Ellis, 2010).…”
Section: Predictor Variables and Predictionsmentioning
confidence: 99%